Stretched graphene nanosheets formed the "obstacle walls" in melamine sponge towards effective electromagnetic interference shielding applications. (15th November 2019) - Guo, Tong; Chen, Xuelong; Su, Lin; Li, Changgeng; Huang, Xiaozhong; Tang, Xiu-Zhi
Abstract: A sort of ultra-light and elastic melamine sponge/graphene composite foam decorated with stretched graphene nanosheets was successfully prepared as electromagnetic interference (EMI) shielding device. For obtaining stretched graphene nanosheets, graphene oxide nanosheets are covered on the pore of melamine sponge formed the"obstacle walls" with the aid of a fluid-assisted method, followed by freeze-drying and reduction treatment. This unique structure is crucial to dissipate electromagnetic waves, due to the formation of more "obstacle walls" and more closed cells for the multireflection. Only a low graphene loading of 0.105 vol%, the composite foam displayed extremely high EMI shielding performance with 37.2 dB, and a specific EMI shielding effectiveness was up to 3410 dB·cm 3 /g owing to the low density of 0.011 g/cm 3 . This work provides a novel methodology to produce graphene/polymer composite porous foam for highly efficient EMI shielding applications. Graphical abstract: Unlabelled Image Highlights: The melamine sponge/RGO foam was prepared by a fluid-assisted method (F-MG foam). Stretched RGO nanosheets formed the "obstacle walls" in the F-MG foam. The F-MG foam shows good electromagnetic interference shielding properties and flexibility.